No evidence of on-farm circulation of avian influenza H5 subtype in Ca Mau Province, Southern Vietnam, March 2016 - January 2017 - Thanh, N; Vy, N; Xuyen, H; Phuong, H; Tuyet, P; Huy, N; Nguyen-Van-Yen, B; Lam, H; Boni, M (Public Library of Science, 2017)
Background: Subtype H5N1 avian influenza viruses, both high pathogenicity and low pathogenicity, have been enzootic in Vietnam since 2001. The viruses are readily identified at live bird markets, but virus prevalence on smallholder poultry is typically zero or very low. If the true direction of the viral transmission chain is farm to market, it is unknown why farm prevalence should be low when market prevalence is moderate to high. Methods: We established a cohort of 50 smallholder poultry farms in Ca Mau province in the Mekong Delta region of Vietnam. From March 2016 to January 2017, we collected naso-pharyngeal and cloacal samples from 156 ducks and 96 chickens. In addition, 126 environmental samples were collected. Samples were assayed for H5 subtype influenza by real-time RT-PCR. Results/Discussion: None of the 378 collected samples were positive for H5 influenza. This is likely to mean that circulation of subtype H5 influenza viruses was low in Ca Mau in 2016. Detection of avian influenza on smallholder poultry farms is necessary to determine the directionality and association between farm prevalence and market prevalence of avian influenza viruses. Larger farm-level studies should be planned as these will be critical for determining the presence and strength of this association.